IMPROVING STUDENTS' PARTICIPATION IN SPEAKING ENGLISH USING SNOWBALL THROWING TECHNIQUE - Nurmalasari, Maulani; Apsari, Yanuarti (IKIP Siliwangi, 2019)
This study aimed to investigate the implementation of snowball throwing technique in teaching speaking and to find out the students’ participation toward the implementation of snowball throwing. This study was conducted at SMK PGRI 1 Cimahi. The students of XI AP 1 class were selected as the respondents of the research. The research used descriptive qualitative method. The data was obtained from classroom observation and students’ interview. The result showed that snowball throwing technique can be used effectively to improve students’ speaking skill through several stages. First, every leader explains the material to their group. Second, every student writing one question about the material. Third, the paper is rolled into a ball and thrown from one student in a group to the other student in another group for approximately 2 minutes. Fourth, after the student gets one ball (one question), he or she is given chance to answer the question. Fifth, every group has their turn to answer the question; the group that gave wrong or incorrect answers and gets the lowest score is given a penalty. Those stages gave the students more chance to interacted in the class. It was very helpful in provide the students with more enjoyable activities which made the students involved in teaching and learning process actively.